Regioselective Vinylation of Remote Unactivated C(sp3)−H Bonds: Access to Complex Fluoroalkylated Alkenes. Issue 5 (28th December 2018) - Wu, Shuo; Wu, Xinxin; Wang, Dongping; Zhu, Chen
Abstract: Regioselective incorporation of a particular functional group into aliphatic sites by direct activation of unreactive C−H bonds is of great synthetic value. Despite advances in radical‐mediated functionalization of C(sp 3 )−H bonds by a hydrogen‐atom transfer process, the site‐selective vinylation of remote C(sp 3 )−H bonds still remains underexplored. Reported herein is a new protocol for the regioselective vinylation of unactivated C(sp 3 )−H bonds. The remote C(sp 3 )−H activation is promoted by a C‐centered radical instead of the commonly used N and O radicals. The reaction possesses high product diversity and synthetic efficiency, furnishing a plethora of synthetically valuable E  alkenes bearing tri‐/di‐/mono‐fluoromethyl and perfluoroalkyl groups. Abstract : Give and take : Regioselective incorporation of a particular functional group into aliphatic sites by direct activation of unreactive C−H bonds remains challenging. Herein a new protocol for the regioselective vinylation of unactivated C(sp 3 )−H bonds is reported. The activation of a remote C(sp 3 )−H bond is promoted by a C‐centered radical instead of the commonly used N and O radicals.